Hardware design for maximum power point tracking (MPPT) based on metaheuristic algorithm in photovoltaic (PV) systems - Darjat, Darjat; Bima, Satria Arya; Evangelista, Hieronimus Emilianus; Winardi, Bambang; Zahra, Ajub Ajulian; Tahir, Nooritawati Md (Eastern-European Journal of Enterprise Technologies, 2024)
PSO and ABC algorithms with Arduino microcontrollers are focused on developing efficient solutions for control systems, energy optimization, and signal processing. These algorithms are generally for platforms with large resources, making them difficult to implement directly on Arduino. Adjustments are needed so that the algorithm can work efficiently without sacrificing the quality of the results. Both are implemented for partially shaded conditions in photovoltaic (PV) systems. The MPPT hardware development method with this meta algorithm can be a solution in dealing with the constraints of partially shaded disturbances. Meanwhile, other studies of the two concepts of the PSO and ABC algorithms have also been developed through software simulations for both MPPT applications and other fields. Evaluation criteria and methods for optimizing MPPT performance have been proposed by implementing a DC-DC Boost Converter. Testing was conducted with a PV with of 47.6 V and Isc of 11.6 A under two conditions to assess the performance of the PSO and ABC. The test resulted in the average power generated by the system with PSO algorithm on three unshaded PV with irradiation of 801 W/m² and a temperature of 84.5 °C with load variations of 50 Ω, 100 Ω, 200 Ω, and 400 Ω was 49.06 W, while the irradiation on one shaded PV at 198 W/m² resulted in an average power of 46.13 W. The system using the ABC algorithm on three unshaded PV generated an average power of 48.35 W, and with irradiation on one shaded solar panel at 198 W/m², it generated an average power of 45.03 W. Overall, the study demonstrates that both PSO and ABC algorithms effectively improve power generation in partially shaded conditions, with PSO showing better performance. These findings suggest that implementing these algorithms can enhance the efficiency of PV systems in practical applications